Dinamika Gender dan Kinerja Perusahaan: Eksplorasi Peran Dewan Wanita dengan Kualifikasi Akuntansi - Ivone Ivone; Sheren Sheren; Budi Chandra (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
Although research topics related to gender influence are quite common, there are still inconsistencies in the results Many countries have implemented gender quotas on company boards, whereas Indonesia has not adopted this policy yet. So this research was conducted to determine the influence of female directors and commissioners on company performance as well as the influence of the moderating variable of women on the board with accounting qualifications. This research uses a purposive sampling method. The objects of this research are all non-financial companies listed on the IDX from 2018 to 2022, accompanied by purposive sampling criteria. This research applies panel data regression analysis methods and uses the SPSS and EViews statistical programs. The results of this research found that female directors and commissioners do not have a positive influence on company performance. Meanwhile, moderating variables can moderate the relationship between independent and dependent variables. However, the direction of moderation obtained shows opposite results to previous research. This can occur due to investor bias, where investors feel unsure about the competence of female board members.